2009
DOI: 10.2353/ajpath.2009.080296
|View full text |Cite
|
Sign up to set email alerts
|

Activin C Antagonizes Activin A in Vitro and Overexpression Leads to Pathologies in Vivo

Abstract: Activin A is a potent growth and differentiation factor whose synthesis and bioactivity are tightly regulated. Both follistatin binding and inhibin subunit heterodimerization block access to the activin receptor and/or receptor activation. We postulated that the activin-␤ C subunit provides another mechanism regulating activin bioactivity. To test our hypothesis, we examined the biological effects of activin C and produced mice that overexpress activin-␤ C . Activin C reduced activin A bioactivity in vitro; in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 46 publications
4
64
1
Order By: Relevance
“…Activin C does not activate activin A-responsive promoters and it was suggested that the beta C subunit down-regulates the levels of bioactive activin A via the formation of signaling-incompetent activin AC heterodimers in PC3 human prostate cancer cells [9,86] . In a recent study from the same group, it was shown that homodimeric activin C inhibited activin A-induced Smad2 phosphorylation and growth inhibition, and that activin beta C transgenic mice develop prostate, testis and liver pathologies suggestive of an activin A antagonistic effect [87] . In line with these observations, elevated beta C immunoreactivity was found in human prostate, testis and liver cancers [87] .…”
Section: Beta C and Beta Ementioning
confidence: 99%
See 1 more Smart Citation
“…Activin C does not activate activin A-responsive promoters and it was suggested that the beta C subunit down-regulates the levels of bioactive activin A via the formation of signaling-incompetent activin AC heterodimers in PC3 human prostate cancer cells [9,86] . In a recent study from the same group, it was shown that homodimeric activin C inhibited activin A-induced Smad2 phosphorylation and growth inhibition, and that activin beta C transgenic mice develop prostate, testis and liver pathologies suggestive of an activin A antagonistic effect [87] . In line with these observations, elevated beta C immunoreactivity was found in human prostate, testis and liver cancers [87] .…”
Section: Beta C and Beta Ementioning
confidence: 99%
“…In a recent study from the same group, it was shown that homodimeric activin C inhibited activin A-induced Smad2 phosphorylation and growth inhibition, and that activin beta C transgenic mice develop prostate, testis and liver pathologies suggestive of an activin A antagonistic effect [87] . In line with these observations, elevated beta C immunoreactivity was found in human prostate, testis and liver cancers [87] . Like beta C, also the beta E subunit is highly expressed in the liver, but has been detected at lower levels in several other tissues as well [7,11,88,89] .…”
Section: Beta C and Beta Ementioning
confidence: 99%
“…The formation of homodimeric activin C (bC-bC), heterodimeric activins AC (bA-bC), BC (bB-bC), and CE (bC-bE), and inhibin C (a-b) has been demonstrated by ectopic expression of the respective subunits in different cell models (Mellor et al 2000;Ushiro et al 2006). Interestingly, activin C (bC-C) does not activate activin A (bA-bA)-responsive promoters, suggesting that the bC subunit regulates the levels of bioactive activin A (bA-bA) through the formation of signalingincompetent activin AC heterodimers (Mellor et al 2003;Butler et al 2005;Gold et al 2009). Therefore, the bC subunit might function as an antagonist of activin function and thereby regulate activin signaling (Mellor et al 2000(Mellor et al ,2003.…”
Section: Discussionmentioning
confidence: 99%
“…However, this subunit has been detected in cells from several other organs, including normal or malignant prostate and ovarian, testicular, endometrial, and pituitary tissues (Loveland et al 1996;Mellor et al 2000;Gold et al 2004Gold et al ,2009Kimmich et al in press). The inhibin bC gene was detected in placental tissue from uncomplicated term pregnancies and pregnancies with preeclampsia (Casagrandi et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation